Tracking HCV protease population diversity during transmission and susceptibility of founder populations to antiviral therapy - Khera, Tanvi; Todt, Daniel; Vercauteren, Koen; McClure, C. Patrick; Verhoye, Lieven; Farhoudi, Ali; Bhuju, Sabin; Geffers, Robert; Baumert, Thomas; Steinmann, Eike; Meuleman, Philip; Pietschmann, Thomas; et al. (Elsevier, 2017)
Due to the highly restricted species-tropism of Hepatitis C virus (HCV) a limited number of animal models exist for pre-clinical evaluation of vaccines and antiviral compounds. The human-liver chimeric mouse model allows heterologous challenge with clinically relevant strains derived from patients. However, to date, the transmission and longitudinal evolution of founder viral populations in this model have not been characterized in-depth using state-of-the-art sequencing technologies. Focusing on NS3 protease encoding region of the viral genome, mutant spectra in a donor inoculum and individual recipient mice were determined via Illumina sequencing and compared, to determine the effects of transmission on founder viral population complexity. In all transmissions, a genetic bottleneck was observed, although diverse viral populations were transmitted in each case. A low frequency cloud of mutations (<1%) was detectable in the donor inoculum and recipient mice, with single nucleotide variants (SNVs) > 1% restricted to a subset of nucleotides. The population of SNVs >1% was reduced upon transmission while the low frequency SNV cloud remained stable. Fixation of multiple identical synonymous substitutions was apparent in independent transmissions, and no evidence for reversion of T-cell epitopes was observed. In addition, susceptibility of founder populations to antiviral therapy was assessed. Animals were treated with protease inhibitor (PI) monotherapy to track resistance associated substitution (RAS) emergence. Longitudinal analyses revealed a decline in population diversity under therapy, with no detectable RAS >1% prior to therapy commencement. Despite inoculation from a common source and identical therapeutic regimens, unique RAS emergence profiles were identified in different hosts prior to and during therapeutic failure, with complex mutational signatures at protease residues 155, 156 and 168 detected. Together these analyses track viral population complexity at high-resolution in the human-liver chimeric mouse model post-transmission and under therapeutic intervention, revealing novel insights into the evolutionary processes which shape viral protease population composition at various critical stages of the viral life-cycle.